2022
DOI: 10.1097/sla.0000000000005709
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of the Additional Benefit of Pharmacological Thromboprophylaxis for Endovenous Varicose Vein Interventions

Abstract: Objective: The primary objective of this systematic review and meta-analysis was to elucidate the rate of venous thromboembolism (VTE) after endovenous interventions for varicose veins in the presence of pharmacological and mechanical thromboprophylaxis versus mechanical thromboprophylaxis alone. Background: The VTE rate after endovenous procedures for varicose veins is higher than other day-case procedures and could be reduced with pharmacological thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…An intrinsic problem in studies of VTE is the heterogeneous risk profile of individual participants. The lack of risk stratification in studies of VTE was recently highlighted in an extensive systematic review and meta-analysis of VTE rates after endovenous interventions for varicose veins, and it was recommended that risk stratification tools, such as the Caprini score, be adopted in future studies 47,48 . In the context of this study, it may be that the participants with the highest risk of VTE stood to gain the most from combined GCS and pharmacological thromboprophylaxis, but unfortunately due to lack of standardized risk stratification, the role of GCS in this context remains uncertain.…”
Section: Discussionmentioning
confidence: 92%
“…An intrinsic problem in studies of VTE is the heterogeneous risk profile of individual participants. The lack of risk stratification in studies of VTE was recently highlighted in an extensive systematic review and meta-analysis of VTE rates after endovenous interventions for varicose veins, and it was recommended that risk stratification tools, such as the Caprini score, be adopted in future studies 47,48 . In the context of this study, it may be that the participants with the highest risk of VTE stood to gain the most from combined GCS and pharmacological thromboprophylaxis, but unfortunately due to lack of standardized risk stratification, the role of GCS in this context remains uncertain.…”
Section: Discussionmentioning
confidence: 92%
“…To address this, we conducted an analysis of 229 study arms, pooling data from 480 581 participants undergoing endovenous interventions. Our approach involved subgroup analyses, comparing those receiving pharmacological thromboprophylaxis and compression versus compression alone, and distinguishing between asymptomatic screen-detected and symptomatic VTE 24…”
Section: Methods and Analysismentioning
confidence: 99%
“…Contradicting NICE guidelines, the routine use of pharmacological thromboprophylaxis for SET has become prevailing practice, despite having no supportive evidence base. A systematic review and meta-analysis published in 2022 failed to identify any high-quality evidence to support current pharmacological thromboprophylaxis strategies in this group of patients 24. However, the study suggested that there is a significant reduction in the rate of DVT with additional pharmacological thromboprophylaxis (1.09% vs 3.20% for pharmacological thromboprophylaxis vs compression alone).…”
Section: Introductionmentioning
confidence: 99%
“…В-третьих, приведенные уровни биомаркеров могут быть следствием не специфического вирусного поражения эндотелия, а банальной гиподинамии на фоне длительного пребывания в изоляции, перехода на дистанционную работу и глобального изменения образа жизни в период пандемии. Предыдущие исследования показали, что даже у здоровых добровольцев без признаков патологии венозной системы возможно обнаружить локальное увеличение концентрации IL-6 в образцах крови из вен нижних конечностей [9], а ортостатическая нагрузка в течение 30-60 мин может спровоцировать повышение уровня таких маркеров эндотелиальной дисфункции, как ELAM-1 (E-селектин), ICAM-1, VCAM-1 (молекулы клеточной адгезии), аннексин V и микрочастицы [10,11]. Таким образом, предполагаемая вирус-индуцированная флебопатия на деле может оказаться хорошо известной ортостатической (гипостатической) функциональной венозной недостаточностью.…”
Section: уважаемая редакция!unclassified